Physiological stress responses and meat quality of goats subjected to different transportation and lairage duration - Raghazli, Razlina (2020)
The main objective of this study was to determine the effect of acute preslaughter stress of different transport (TS) and lairage (L) duration on the physiological stress indicators and meat quality of goats. Eighteen male goats were grouped into six groups which are the TS2L3, TS2L6, TS2L12, TS6L3, TS6L6 and TS6L12. Goats were transported for two or six hours, kept in the lairage according to the designated time and slaughtered. Samples were obtained at the farm level (T1), after transportation (T2), after lairage (T3) and during slaughter (T4). EEG were recorded and blood were samples for the analysis of the haematological, blood biochemistry changes, cortisol, Triiodothyronine (T3) and thyroxine (T4) concentration. Longissimus lumborum (LL) muscles were sampled on day 0, 1, 3 and 7 post-mortem days for the analysis of meat quality, lipid peroxidation, HSP27 expression and apoptosis rate. Two-hour transportation (TS2) resulted in higher EEG activity than the six hour transportation (TS6) duration (P< 0.05). At the same time, transportation stress significantly increased the neutrophil and monocyte counts and neutrophil-lymphocyte ratio (N/L ratio). Lairage time has a significant impact on the EEG analysis during slaughter. Long transport and lairage duration increased the time for the EEG to reach isoelectric, increase the RBC, PCV and plasma protein level, cortisol concentration, cellular apoptosis index and affect the meat quality (P < 0.05). The TS6 group produced meat which were higher in pH, darker in colour than the TS2 group. However, the TS2 group produced juicier meat than the TS6 group. More than three-hour lairage in the TS2 group and more than six-hour lairage for the TS6 group was needed for the meat quality to improve. Ageing was crucial in improving meat quality. Most of the stress effects were diminished after three to seven days of ageing. In conclusion, transport and lairage duration produce a significant impact on the physiological stress response and the meat quality of goats.